Plant genetic resources and food security in West and Central Africa: Regional Conference, 26-30 April 2004 - Vodouhe, R.; Atta-Krah, Kwesi; Achigan-Dako, Enoch G.; Eyog-Matig, O.; Avohou, H. (2007)
The Regional Conference on Plant Genetic Resources and Food Security in West and Central Africa was held at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria from 26 to 30 April 2004. Ninety-five scientists and agricultural research managers from 13 countries and 18 institutions and organizations attended the conference that was organized under the auspices of Conseil Ouest et Centre Africain pour la Recherche et le Développement (CORAF). It took about two years to organize it. Partner institutions including the Conference of Directors for Agronomic Research in West and Central Africa (CORAF), Bioversity International, the International Institute of Topical Agriculture (IITA), Food and Agriculture Organization (FAO), the West Africa Rice Development Association (WARDA), the International Crops Research Institute for Semi-Arid Tropics (ICRISAT), the Desert Margin Programme (DMP), the World Agroforestry Centre (ICRAF), the System-Wide Genetic Resources Programme (SGRP) and the Genetic Resources Policy Initiative (GRPI) co-funded and organized the conference assisted by the Technical Centre for Agricultural and Rural Cooperation (CTA) and Syngenta. The main outcomes from the deliberations are presented in this synthesis report. The main goal of the conference was to provide a forum for assessing the state of plant genetic resources (PGR) conservation and management in West and Central Africa (WCA), and to explore methods of strengthening regional collaboration. The specific objectives were: To assess the state of, and mechanisms for, management and sustainable use of plantgenetic resources in WCA countries;To enhance awareness on new global and regional plant genetic resources (PGR)developments and policy frameworks;To establish mechanisms and strategies for promotion of collaboration and coordination at regional and country levels on PGR conservation, management and policies in the sub-region. This conference gave a unique opportunity to scientists in WCA to assess the state of genetic resources conservation, management and use in the sub-region. They explored mechanisms for strengthening regional collaboration and discussed how these resources can be managed to solve food insecurity in the region. The national research institutes, under the framework of CORAF and the various CGIAR Centres (Bioversity, IITA, WARDA, ICRISAT) working in WCA, and FAO decided to work closely together for the benefit of genetic resources. Many initiatives are already being developed in the region and the conference emphasised the necessity to link all those initiatives and to ensure that the region is not left out in genetic resources conservation and use. The conference ended with a declaration and communiqué.